Pengaruh Intervensi Self-Management terhadap Self-Care dan Tekanan Darah pada Pasien Hipertensi - Nyayu Nina Putri Calisanie; Herdiman; Linlin Lindayani (Risenologi, 2021)
Hypertension is a major cause of premature death worldwide with a high prevalence and is one of the main risk factors for various chronic diseases such as heart and kidney disease. The Hypertension is a major cause of premature death worldwide with a high prevalence and is one of the main risk factors for various chronic diseases such as heart and kidney disease.The purpose of this study was to determine the effectiveness of an intervention that combines self-management on self-care and blood pressure in hypertensive patients. The type of research used is quaesy experience with two groups. The sample in this study were hypertensive patients in the work area of the puskesmas in Bandung, West Java. The inclusion criteria in this study were 35-85 years old, taking two or less antihypertensive drugs for hypertension, having a blood pressure of more than 140/90 mmHg. The number of samples is estimated to require as many as 66 hypertensive patients.Before the intervention, respondents showed lower self-care, with an average score of 1.35 (SD=0.73). The self-care score increased over time as respondents in the intervention group by 3.21 (SD=1.44), and respondents in the control group by 2.52 (SD=10.78) at T2. Blood pressure decreased at T2 in the intervention group with a systolic score of 128.1 (SD=11.62), and respondents in the control group got a systolic score of 137 (SD=15.15). The self-management program improved outcomes relative to controls at T1 across four outcomes: 1) self-care scores improved 8.7% (95% CI 0.021-0.149) and blood pressure slightly improved 8.8% (95% CI 0.017-0.125) . At T2, improvements in outcomes relative to controls were still observed in self-care scores and blood pressure.The results of this study will provide recommendations to hypertensive patients and health workers in Indonesia regarding self-management to control blood pressure, diet, and medication, so that they can be used in daily practice.